Kinetic Isotopic Degassing of CO2 During the 2021 Fagradalsfjall Eruption and the δ13C Signature of the Icelandic Mantle - Yves Moussallam; Estelle F. Rose‐Koga; Tobias P. Fischer; Guillaume Georgeais; Hyun Joo Lee; Janine Birnbaum; Melissa A. Pfeffer; Talfan Barnie; Edouard Regis (Geochemistry, Geophysics, Geosystems)
Abstract CO2 is the first volatile to exsolve in magmatic systems and plays a crucial role in driving magma ascent and volcanic eruptions. Carbon stable isotopes serve as valuable tracers for understanding the transfer of CO2 from the melt to the gas phase during passive degassing or active eruptions. In this study, we present δ13C measurements from the 2021 Fagradalsfjall eruption, obtained from (a) volcanic gases emitted during the eruption and collected via unmanned aerial systems (UAS), and (b) a series of mineral‐hosted melt inclusions from the corresponding tephra deposits. These data sets jointly track the carbon isotopic evolution of the melt and gas phases during the last 10 km of magma ascent. The isotopic evolution of both phases indicates that kinetic degassing, a process previously only identified in mid‐ocean ridge basalts, took place in the 10 to 1 km depth range, followed by equilibrium degassing at near‐surface conditions in the last kilometer. Postulating that the melt was first saturated with CO2 at 27 km depth and that degassing from then to 10 km depth took place via equilibrium isotopic fractionation, the melt inclusion data constrain the initial δ13C signature of the Icelandic mantle to −6.5 ± 2.5‰ but also show indications of possible isotopic heterogeneity in the mantle source.